2019
DOI: 10.1088/1367-2630/ab51fe
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution hard-x-ray photoelectron diffraction in a momentum microscope—the model case of graphite

Abstract: Hard x-ray photoelectron diffraction (hXPD) patterns recorded with a momentum microscope with high k-resolution (0.025 Å −1 equivalent to an angular resolution of 0.034°at 7 keV) reveal unprecedented rich fine structure. We have studied hXPD of the C 1s core level in the prototypical low-Z material Graphite at 20 photon energies between 2.8 and 7.3 keV. Sharp bright and dark lines shift with energy; regions of Kikuchi band crossings near zone axis exhibit a filigree structure which varies rapidly with energy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…The agreement of Figure 10(f-h) with experiment Figure 10(a-c) is excellent. Strikingly good agreement between measured hXPD diffractograms and Kikuchi patterns calculated by the Blochwave approach have also been found for graphite [204] and Si [205,226], i.e. for light elements with their relatively small scattering factors.…”
Section: 14mentioning
confidence: 56%
See 3 more Smart Citations
“…The agreement of Figure 10(f-h) with experiment Figure 10(a-c) is excellent. Strikingly good agreement between measured hXPD diffractograms and Kikuchi patterns calculated by the Blochwave approach have also been found for graphite [204] and Si [205,226], i.e. for light elements with their relatively small scattering factors.…”
Section: 14mentioning
confidence: 56%
“…The increasing sharpness and sensitivity with increasing energy is clearly visible in the sequence of hXPD patterns for graphite between E final = 2.6 and 7 keV. [204] XPD differs in several respects from conventional diffraction. The most important practical aspect is the element specificity based on addressing a specific core level.…”
Section: 14mentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, high‐energy photoelectron diffraction (hologram) patterns of graphite with high kinetic energies (>2.4 keV) have been reported. [ 12 ] In this study, they assumed that the line‐shaped pattern in the hologram was formed by the normal Kikuchi band process. It has been found that the quasi‐Kikuchi band in the photoelectron hologram, with a kinetic energy of several hundreds of eV, has two different formation mechanisms.…”
Section: Introductionmentioning
confidence: 99%